DIJKSTRA ALGORITHM IN DETERMINING THE SHORTEST ROUTE FOR DELIVERY SERVICE BY J&T EXPRESS IN BANDUNG - Anie Lusiani; Siti Samsiyah Purwaningsih; Euis Sartika (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The determination of the shortest route can be done using various methods, one of which is the Dijkstra algorithm. This algorithm is often used in routing problems with minimum weight in computer networks, communication networks and transportation networks. There are several applications of the Djikstra algorithm, namely solving the problem of the shortest path of neutrosophy, mapping tourism potential, and developing geographic information systems in the health sector. In this research, Dijkstra algorithm will be applied to optimize the mileage of the delivery of goods packages. Data and information namely the address, weight and number of customer packages carried by a courier in one delivery trip are obtained from the drop point of PT. J&T Express in Sarijadi area of Bandung City. Meanwhile, data about mileage is obtained from the Google Maps application. All this data is used to construct an initial model graph that is a connected weighted graph, where the location of a drop point or a customer is a vertex and a road connecting two locations is an edge on the graph. The weight in this graph is the mileage from the drop point to the customers or from one customer to another. Then, the Djikstra algorithm is run on this graph where the drop point is the starting point of the route, so that the courier visits all customers and returns again to the drop point. The resulting route is a cycle in the graph which is the shortest closed route at 1890 meters.